First person - Wedad Fallatah and Tara Smith (The Company of Biologists, 2020)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Wedad Fallatah and Tara Smith are co-first authors on 'Oral administration of a synthetic vinyl-ether plasmalogen normalizes open field activity in a mouse model of rhizomelic chondrodysplasia punctata', published in DMM. Wedad is a PhD student in the lab of Dr Nancy Braverman at the Research Institute of the McGill University Health Center and McGill University, Montreal, QC, Canada, investigating mouse models to characterize and establish preclinical therapeutic interventions for rhizomelic chondrodysplasia punctate (RCDP). Tara is Vice President of Therapeutics in the lab of Dr Shawn Ritchie at Med-Life Discoveries LP, Saskatoon, SK, Canada. Her research focuses on evaluating plasmalogen precursors as potential therapeutic agents for the treatment of peroxisomal disorders such as RCDP, as well as neurodegenerative diseases of aging including Alzheimer's disease, Parkinson's disease and multiple sclerosis.